Fabrication and characterisation of Pickering emulsion-based oleogel stabilised by citrus fibre and whey protein isolate colloidal complex: application in cookie formulation - Genc, Ezgi; Karasu, Salih; Akcicek, Alican; Toker, Omer Said (WILEY, 2024)
In this study, the oleogel was produced by Pickering emulsion-based method by using citrus fibre (CF)-whey protein isolate (WPI) colloidal complex. The obtained oleogels were characterised by rheological and textural properties, and then the oleogels were used in cookies as an alternative to palm oil. The four oleogels (1% to 5%) were fabricated using a CF-10% WPI complex. Shear thinning rheological behaviour was observed in all emulsion and oleogel samples. The G values were greater than the G values, indicating that solid-like behaviour dominated in all emulsion and oleogel samples. All oleogel samples had a higher than 90% oil-holding capacity. The visual appearance of 3% CF-10% WPI and 5% CF-10% WPI showed no surface oil, and more integrity structure means that could well trap oil in a gel matrix. Increasing CF% concentration reduced oil droplets and created a more compact structure, particularly at 3% and 5% CF-10% WPI. An increase in CF concentration from 2% to 5% led to an increase in the hardness value of the dried products and cookies that CF formed a 3D network structure with binds liquid oil. The oxidative stability showed that no significant changes were found between the 3% CF-10% WPI and palm cookies (P < 0.05). Cookies containing oleogels with a 3% CF content exhibited a visual resemblance to this trait, suggesting a colour appearance that closely resembled cookies made with palm oil. The incorporation of oleogels into the cookie recipe proved to be an effective substitute for palm oil. CF-10% WPI oleogels show promise for use in cookie preparation as a replacement for palm oil, offering potential as substitutes for saturated and trans fats in food products.
Keywords: Citrus fibre; emulsion templated; oleogel; palm oil; whey protein isolate; INTERNAL PHASE EMULSIONS; OIL; WAX; Food Science & Technology